Effects of C/N ratio and substrate addition on natural food communities in freshwater prawn monoculture ponds - Asaduzzaman, Md.; Rahman, Mohammad Mustafizur; Azim, M. Ekram; Islam, Md. Ashraful; Wahab, Md. Abdul; Verdegem, Marc; Verreth, Johan (Elsevier B.V., 2010)
An on-station trial was conducted to investigate the effects of three C/N ratios (10/1, 15/1 and 20/1) along with substrate presence or absence on natural food communities in freshwater prawn culture ponds. An experiment was carried out in 40 m2 ponds stocked with a stocking density of 2 prawn juveniles (5.023 ± 0.02 g)m−2. A locally formulated and prepared feed containing 30% crude protein with C/N ratio 10 was applied to all ponds. In order to raise the C/N ratio of the feed input to 15 and 20, tapioca starch was applied separately as a source of carbohydrate in addition to the artificial feed. Under substrate treatments, bamboo side shoots were posted vertically in pond bottoms resulting in 100% additional surface area as periphyton substrates. The treatments with different C/N ratios are referred to as “CN10”, “CN15” and “CN20”. Increasing the C/N ratio from 10 to 20 significantly increased the biovolume of phytoplankton, crustaceans and rotifers in the water column by 15%, 6% and 11%, respectively. The biovolume of periphyton was 50% higher in treatment CN20 compared to treatment CN10. Increasing the C/N ratio from 10 to 20 raised the biovolume of total heterotrophic bacteria(THB) in the water column (70%), sediment (36%) and periphyton (40%). The chironomids biovolume was also significantly higher (28%) in treatment CN20 compared to treatment CN10. The addition of substrates decreased the biovolume of water column plankton by 14% but the combined biovolume (plankton+periphyton) was almost double in substrate-added ponds. The biovolume of plankton, periphyton and THB increased significantly with culture time duration whereas the biovolume of benthic macroinvertebrates decreased significantly with culture time indicating that freshwater prawn grazed on them. A significant interaction between C/N ratios and substrate presence or absence was only observed for plankton biovolume in the water column. This study demonstrated that plankton, periphyton and microbial biofloc communities were under-utilized by the freshwater prawn in treatment CN20. This leaves room for increasing the stocking density of prawn and/or inclusion of periphyton grazing fish species to improve nutrient utilization efficiency and overall sustainability.